1915 - San Francisco, March Song - S. and P.I. Jacoby::::::::: (P.I. Jacoby)
Piano and vocal score, 5 p. On cover: Respectfully dedicated to the ladies & gentlemen who are striving to make the P.P.I.E. the greatest in history. At head of p.[2]: Souvenir editionExposition prize song. Advertisements on p.[2]. Text of ad by Hathaway & Skrupa, selling agents in California Counties Building at Panama-Pacific Exposition Grounds: This song was proclaimed the prize winner in the San Francisco Bulletins Exposition Song Contest.